'The Great Debate': Welfarism, Objectivity, and Cold War Ideology in the Workers' Educational Association. Issue 1 (April 2019) - Efstathiou, Christos
Abstract : During the early 1950s, much of the debate within the Workers' Educational Association (WEA) concerned the direction of the organization. Sidney G. Raybould, director of the Leeds extramural department, argued that 'university standards' should apply to extramural work. His views were adopted at the 1951 Annual WEA Conference, when it was decided that more university-style tutorial classes should be organized. Several tutors saw this move as elitist and out of touch with working people: they claimed that above all the role of the WEA was to create a social movement capable of increasing political awareness among its members. The internal discussions seemed to pull the WEA in two different directions, one supporting implementation of 'university standards' and another against this. R.D. Waller, an extramural director, called this the 'Great Debate'. The clash of opinions caused frustration in several adult educators who felt that the role of the WEA was seriously weakened. This article tries to reassess the history of the debate.